Exploring the effectiveness of corpus-driven learning in teaching lexical collocation to Pakistani undergraduates - Imran Shah, Muhammad (2024)
Foreign language acquisition is more likely to increase if the attention of the learners is consciously drawn to linguistic features. The direct exposure of certain features from corpora like collocation helps EFL/ESL non-native learners in language acquisition. The present research study explains the effect of corpus-driven language learning (CDLL) on Pakistani EFL undergraduates and explores the opinion of language users about it. The experimental research design following mixed-method approach has been applied to 100 undergraduates, comprising 50 students for experimental and 50 for the control group from the department of Applied Linguistics GC University Faisalabad Pakistan. In a pre-test the knowledge of lexical collocations of learners were evaluated; data was collected quantitatively to measure the results of both groups to test the p-value from t-score. Then, among the sample of the study, the experimental group were undergone explicit learning with the compilation of adhoc corpora of editorials of Pakistani and British newspapers to look for certain lexical patterns under the supervision of the teacher and compared the lexical collocations they extracted in both corpora. In this case, learners became researchers and language became data (Boulton, 2018). Whereas, the control group was treated with traditional approaches in teaching English collocations. After experimental treatment of one semester (16 weeks), the results of the post-test revealed that CDLL method affected positively and enhanced the knowledge of lexical collocations more among the experimental group than the control group as the p-value of the data decreased. Then a semi-structured interview was conducted among the participants of the experimental group and the faculty members of the department to seek their opinion about the effectiveness of corpus-driven language learning (CDLL). The study has strong pedagogical implications for academicians and researchers regarding the importance of CDLL in the course design of ELT Methods and Approaches.